Implementing Religious Moderation Values at Islamic Schools in Indonesia - Zulfa, Siti; Defianty, Maya; Mulyati, Yatni Fatwa (Muslim Education Review, 2025)
Religious diversity in Indonesia demands its citizens to be moderate as they encounter religious affairs in society. Educators have made substantial efforts in many contexts, including in Madrasah Aliyah, to enable students to embrace the values of religious moderation not only in academic settings but also on a daily basis. This study aims to identify how a Madrasah Aliyah promotes religious moderation values, including students’ responses towards the notion. This study used a qualitative approach and case study design. The research instruments used questionnaires and semi-structured interviews. This study was situated in the scope where the school implements Islamic concepts in learning, which involved a teacher and 32 students. The data for this study is gathered from questionnaires and interviews. The study found that the values of religious moderation are promoted through learning activities supported by the school’s system. Being fair, tolerant, respecting differences, helping others, being honest, humble, cooperative, peaceful, responsible, and being a role model are religious moderation values promoted by the school. These values are embedded in all stages of learning. Also, this study discovered that teachers and students have implemented religious moderation values during teaching and learning. This study has shed light on how religious moderation values can be implemented in Madrasah Aliyah, and students can integrate those values into academic and actual life conditions.